A review on microbial-integrated techniques as promising cleaner option for removal of chromium, cadmium and lead from industrial wastewater. (June 2022) - Kumar, Vinay; Dwivedi, S.K.; Oh, Seungdae
Abstract: Industrial and developmental activities have raised heavy metal loads in wastewater and their inappropriate treatment before disposal causes grave dilemma to the environment. Chromium (Cr), cadmium (Cd) and lead (Pb) are highly toxic heavy metals and extensively used hence, excessively generated with disposing effluent from the industries like paint, battery, electroplating, tannery, paper and pulp, textile, smelting and mining has raised the public attention owing to health concerns. Microbial-remediation processes are considered as environmentally benign options and their integration with existing treatment techniques can construct advanced types of systems in terms of their cost and efficiency due to their synergistic action. These microbial-integrated techniques are gaining popularity these days. There are varieties of microbial-integrated strategy which has been investigated carefully for efficient removal of Cr, Cd, and Pb and has been published in leading journals. In this review, we have critically discussed the microbial–integrated strategies and recent advances in microbial-integrated techniques for proficient removal of Cr, Pb, and Cd from industrial wastewater in a cheaper and cleaner way. In addition, the advantages and disadvantages of the integrated system also have been discussed in this review. The microbial integrated systems such as bioelectrochemical, photo-bioelectrochemical, nano-microbial, and constructed wetland showed excellent performance and have tremendous potential for large scale exploitation. To conclude, microbial-integrated techniques proved as excellent remedial options for Cr, Pb and Cd contaminated wastewater that has been discussed well in this review. These integrated processes may be cost-effective, viable, more efficient and less time taking than the existing techniques and have intense opportunity. Graphical abstract: Unlabelled Image Highlights: Microbial integrated (MI) strategies have been reviewed in this article. MI strategies are the combo of conventional and advanced microbial based techniques. MI strategies are more efficient and appropriate than the other existing techniques. MI techniques have excellent opportunities in Cr, Cd and Pb polluted wastewater treatment.